Vixapatin (VP12), a C-Type Lectin-Protein from Vipera xantina palestinae Venom: Characterization as a Novel Anti-angiogenic Compound - Momic, Tatjana (MDPI, 2012)
A C-type lectin-like protein (CTL), originally identified as VP12 and lately named Vixapatin, was isolated and characterized from Israeli viper Vipera xantina palestinae snake venom. This CTL was characterized as a selective α2β1 integrin inhibitor with anti-melanoma metastatic activity. The major aim of the present study was to prove the possibility that this protein is also a potent novel anti-angiogenic compound. Using an adhesion assay, we demonstrated that Vixapatin selectively and potently inhibited the α2 mediated adhesion of K562 over-expressing cells, with IC(50) of 3 nM. 3 nM Vixapatin blocked proliferation of human dermal microvascular endothelial cells (HDMEC); 25 nM inhibited collagen I induced migration of human fibrosarcoma HT-1080 cells; and 50 nM rat C6 glioma and human breast carcinoma MDA-MB-231 cells. 1 µM Vixapatin reduced HDMEC tube formation by 75% in a Matrigel assay. Furthermore, 1 µM Vixapatin decreased by 70% bFGF-induced physiological angiogenesis, and by 94% C6 glioma-induced pathological angiogenesis, in shell-less embryonic quail chorioallantoic membrane assay. Vixapatin’s ability to inhibit all steps of the angiogenesis process suggest that it is a novel pharmacological tool for studying α2β1 integrin mediated angiogenesis and a lead compound for the development of a novel anti-angiogenic/angiostatic/anti-cancer drug.